Digitalization of Government and Public Trust: A Case Study of E-KTP and Data Governance in Indonesia - Wahyu Eko Saputro (PT. Publikasiku Academic Solution, 2025)
Digital transformation in governance is a key strategy in improving the efficiency and transparency of public bureaucracy. However, in Indonesia, the implementation of digital services such as e-KTP is still faced with challenges related to public trust, especially in terms of data protection and service transparency. This study aims to analyze the influence of data governance quality on the level of public trust in government digital services. The method used is a mixed-method approach with a sequential explanatory strategy. Data was collected through an online survey of 300 respondents from three provinces, as well as in-depth interviews with 12 key informants consisting of officials, academics, and users of e-KTP services. The data were analyzed using linear regression and thematic analysis. The results of the study show that the protection of personal data is the most significant variable in forming public trust, followed by transparency and accessibility of services. The fluctuations in public trust in the past five years indicate that the success of digitalization depends heavily on strengthening data governance and not just modernizing technology. The research recommends the establishment of independent supervisory bodies for data protection, public involvement in digital policy evaluations, and the integration of digital literacy as part of national programs. Thus, government digitalization can develop in an inclusive, transparent, and sustainable manner.